2017
DOI: 10.1016/j.joca.2017.02.793
|View full text |Cite
|
Sign up to set email alerts
|

Different doses of strontium ranelate and mechanical vibration modulate distinct responses in the articular cartilage of ovariectomized rats

Abstract: SrR and vibration modulate distinct responses in cartilage. Combined treatment accelerates degeneration. In contrast, SrR treatment at 300 mg/kg/day attenuates osteoarthritis (OA) progression, improving cartilage matrix quality and preserving cell viability in ovariectomized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…The expression of MMP-9 was not altered with the use of SrRan. Contrary to what was found in a previous study, no reduction in TNF-α expression was observed in this study ( 33 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The expression of MMP-9 was not altered with the use of SrRan. Contrary to what was found in a previous study, no reduction in TNF-α expression was observed in this study ( 33 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Oophorectomy has also been used for the induction of osteoporosis and osteoarthritis in rats by establishing early menopause. Either 300 or 625 mg·kg −1 ·day −1 of SrRan associated with vibratory stimuli, or not, were used for histological investigation of articular cartilage quality, as well as immunohistochemical analysis for caspase-3, collagen type II, TNF-α, and MMP-9 ( 33 ). It is worth mentioning that the expression of caspase-3 is related to cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the expression of TNF-α without changes in leukocyte count and IL-1β levels was also observed in another pre-clinical study of periarticular tissue samples, with lower doses of SrRan (up to 50 mg/kg/day) ( Alves et al, 2017 ). These results were not confirmed in a study with rats subjected to oophorectomy and treated with SrRan at doses of 300 and 625 mg/kg/day, with no reduction of TNF-α and MMPs, which are metal-dependent endopeptidases that remodel the extracellular matrix ( Mierzwa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
“…In rats subjected to oophorectomy, SrRan at doses of 300 mg/kg/day effectively attenuated the progression of OA, improving the quality of cartilaginous matrix by directly stimulating the synthesis of proteoglycans Furthermore, the cellular viability in those animals was preserved, with lower OARSI scores and reduced expression of caspase-3, an enzyme associated with apoptosis. This effect was abrogated with daily doses of 625 mg/kg associated with mechanical vibration ( Mierzwa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation